Assessment of soil and soil-water salinity in Ben Tre province by electromagnetic technology - Thanh, Le Ngoc; Dung, Nguyen Quang; Tung, Luu Hai (Vietnam Journal of Marine Science and Technology, 2020)
Assessment of soil and soil-water salinity is essential in agricultural production, therefore it is necessary to find out the non-costly, effective, rapid and reliable integrated methodology for this purpose. The paper presents the results of using the electromagnetic induction instrument EM31-MK2Ô in combination with collecting and analyzing soil and soil-water samples, and applying GIS and geostatistical techniques to assess the current status of soil and soil-water salinity in Ben Tre province. Apparent soil electrical conductivity ECa measured from ground surface to 6 m in depth increases from inland to the sea in northwest - southeast direction; ECa is closely related to topsoil salinity to 30 cm deep and to soil-water salinity at depth of 10–100 cm. Current status of soil and soil-water salinity in 2018 was assessed with a 4-fold increase in information, from 16 km2/data point to 4 km2/data point. Consequently four maps were established, consisting of electrical conductivity ECe and total solube salt TSS distributions of soil; electrical conductivity σw and total dissolved solid TDS distributions of soil-water.